A cellular bilayered scaffolds for osteochondral tissue regeneration - Canadas, Raphael Faustino (2014)
Last decade 9.6% of the men and 18% of the woman with more than 60 years presented symptomatic Osteoarthritis [1]. Despite the progress already achieved in osteochondral (OC) repair, some limitations still needs to be overcome. A promising strategy includes a scaffold presenting two regions with different physical characteristics. The use of an acellular structure capable of recruiting the cells during the in vivo OC repair could be a faster and more efficient approach to translate into the clinics. This work aims to develop bilayered gellan gum (GG)/gellan gum-hydroxyapatite (HAp) freeze-dried scaffolds for OC regeneration.